2022
DOI: 10.3389/fenvs.2022.1018540
|View full text |Cite
|
Sign up to set email alerts
|

Strengthen or weaken? Research on the influence of internet use on agricultural green production efficiency

Abstract: With the rise of “Internet + Agriculture”, existing related research has focused on the impact of Internet use on agricultural productivity. However, few studies have considered the impact on agricultural green production efficiency. This paper employed the SBM model to calculate the agricultural green production efficiency using the observation data of 459 farmers in Shaanxi, Shanxi, and Henan provinces. Further, the influencing factors, their nonlinear impact, and even the effect of using the internet on agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Therefore, the International Cooperative Alliance (ICA) believes that when the environmental awareness of farmers is weak [7] and policies to promote the adoption of AGPTs by farmers are not as effective as they should be, it is possible to enhance the adoption of AGPTs by farmers through the development of "education, training, and information" through cooperatives [8]. This provides an important idea for this study: to protect the agricultural ecological environment, it is not only necessary to change the agricultural production mode [9] but it is also necessary for farmers to actively adopt AGPTs [10], aim to reduce the adverse impact on the environment in the agricultural production process, improve production efficiency, and protect the quality and safety of agricultural products. At the same time, the educational guidance of cooperatives [6] makes farmers realize the importance and advantages of AGPTs and promotes the transformation of farmers' production and operation into greener production methods [11], thus promoting the development of Chinese agriculture towards the goal of greening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the International Cooperative Alliance (ICA) believes that when the environmental awareness of farmers is weak [7] and policies to promote the adoption of AGPTs by farmers are not as effective as they should be, it is possible to enhance the adoption of AGPTs by farmers through the development of "education, training, and information" through cooperatives [8]. This provides an important idea for this study: to protect the agricultural ecological environment, it is not only necessary to change the agricultural production mode [9] but it is also necessary for farmers to actively adopt AGPTs [10], aim to reduce the adverse impact on the environment in the agricultural production process, improve production efficiency, and protect the quality and safety of agricultural products. At the same time, the educational guidance of cooperatives [6] makes farmers realize the importance and advantages of AGPTs and promotes the transformation of farmers' production and operation into greener production methods [11], thus promoting the development of Chinese agriculture towards the goal of greening.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of green perceptions on the adoption of AGPTs may also be different among farmers who participate or do not participate in cooperatives. Therefore, the relationship between cooperative participation and AGPT adoption behavior also requires attention to the important contextual factor of green perception [10,20].…”
Section: Introductionmentioning
confidence: 99%
“…This includes fine planting in fields, facilities, and greenhouses; agricultural products quality and safety supervision; monitoring agricultural production environmental data (such as soil temperature and humidity, nitrogen and oxygen content, environmental temperature and humidity, light intensity, CO 2 concentration, etc. ); providing scientific basis for crop production management; providing the best production conditions for crops; effectively improving crop yields and the overall efficiency of agriculture; thereby promoting the level of automation and intelligence in agriculture (Yu and Bai, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Xie further demonstrated that Internet usage was more effective in reducing poverty for full-time farmers than for part-time and non-farmers [10]. Scholars have further explored the specific paths through which farmers use the Internet to increase their income, finding that Internet usage could affect farm household income mainly by raising the selling price of agricultural products [11], increasing total factor productivity [12], promoting off-farm employment [13], and pulling entrepreneurship [13].…”
Section: Introductionmentioning
confidence: 99%